Автоматизований вимірювальний комплекс для визначення концентрації мінеральних елементів у живильних розчинах - Синявський, О. Ю.; Несвідомін, А. В. (Energy and Automation, 2017)
Automated measuring COMPLEX for determining the concentration of mineral elements in the nutrient solutionA. Sinyavsky, A. Nesvidomin Intensive cultivation technology of vegetables in buildings protected ground based on the systematic control of nutrient solutions and plant products to create a balanced regime of mineral nutrition of plants through proper fertilization.In recent years, widely used method of potentiometric analysis, which largely eliminated the shortcomings inherent optical methods.Significant reserve in expanding functionality, improving accuracy and productivity potentiometric method offers automated calibration and measuring the concentration of mineral elements with the use of computer technology.The purpose of research is to develop automated measuring complex to determine the concentration of mineral elements in the nutrient solution, which makes it possible to reduce labor costs pursuant agrochemical analysis and extend the functionality of the analyzers through a comprehensive analysis of the automation of calibration, measurement and processing of the measurement results.Materials and methods of research. Automated measuring system is designed for determining the concentration of mineral elements (ammonium and nitrate nitrogen, potassium, calcium, magnesium, sodium, chlorine, copper, boron) and pH in nutrient solutions and plants potentiometric method.On the basis of methods for determining the concentration of mineral elements in plants and nutrient solutions, analysis of experience creating ionomer conducted research ionoselective electrodes on the basis of the existing components defined technical requirements for creating automated measuring complex:Results. Measuring complex contains ionoselective measuring electrodes hlorsribnyy auxiliary electrode resistance thermometer, placed on a tripod and a cable connected to the measuring transducer. Measuring transducer consists of a switch, control unit, high-resistance transducer, transducer resistance-voltage ADC PC system unit, display and power supply.The temperature of the solution is measured by a thermometer Resistance 3, the signal of which goes to the transducer-voltage resistance. The voltage is proportional to the temperature of the solution, fed to the input of the switch.Emf electrode system, introduced in a controlled trial, also receives the inputs of the switch, which in turn connects ionoselective measuring electrodes and voltage-converter resistance to high-resistance input converter, where the signal amplification and standardization. The output of high-resistance transducer normalized analog signal entering the ADC, which is converted into digital code and then enters the information bus system unit PC, where it is working on a predetermined algorithm. System unit shall manage the switch through a matching device. The analysis results are displayed.Algorithmic and software dialog mode the computer user by direct potentiometric measurement includes work in the following modes:1. Initial setup configuration.2. Calibration of electrodes.3. Measuring the concentration of mineral elements.ConclusionsDeveloped automated measuring system that provides calibration of the electrode and measuring the concentration of mineral elements direct potentiometric method. In signal processing primary measuring converters accounted electrode selectivity ratios, humidity and dilution of the sample solution temperature, which allows to increase the accuracy of measurement results.Measurement error emf less than 0.5 mV, temperature 0 25 ° C and a concentration of 3%, which meets the technical requirements that apply to measuring complex.